2008
DOI: 10.1002/path.2318
|View full text |Cite
|
Sign up to set email alerts
|

The methylator phenotype in microsatellite stable colorectal cancers is characterized by a distinct gene expression profile

Abstract: The CpG island methylator phenotype (CIMP) in colorectal tumours can be recognized by an increased frequency of aberrant methylation in a specific set of genomic loci. Because of the strong association of CIMP with high microsatellite instability (MSI-H), the identification of CIMP+ tumours within microsatellite stable (MSS) colorectal cancers may not be straightforward. To overcome this potential limitation, we have built an improved seven-locus set of methylation markers that includes CACNA1G, IGF2, RUNX3, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
42
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 13 publications
2
42
1
Order By: Relevance
“…Although this subgroup was small, the result was consistent in both patient groups and was largely independent of potential confounding factors. Some studies, however, have reported contradictive findings (20,24,27,31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although this subgroup was small, the result was consistent in both patient groups and was largely independent of potential confounding factors. Some studies, however, have reported contradictive findings (20,24,27,31).…”
Section: Discussionmentioning
confidence: 99%
“…A poor prognosis in CIMP-high CRC patients might result from other factors closely related to CIMP, such as the BRAF V600E mutation, rather than to an effect of the phenotype itself (20,22,26,27). MSI is another prime candidate, given its tight association with CIMP, but MSI is predictive of a better prognosis (28).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] CIMP colorectal cancers are associated with clinicopathological features such as proximal location, poor grade, presence of tumor-infiltrating lymphocytes, and mucinous differentiation, as well as frequently demonstrating molecular somatic events including the BRAF p.V600E mutation and high levels of microsatellite instability, but with much lower levels of TP53 mutation than their chromosomal unstable colorectal carcinoma counterparts. [6][7][8][9][10][11][12] Mucins are high-molecular weight proteins characterized by the presence of large amino acid tandem repeat sequences that show allelic size variation. Secreted or gel-forming mucins comprise five known types: MUC2, MUC5AC, MUC5B, MUC6, and MUC19.…”
mentioning
confidence: 99%
“…Thus, based on CIN, these tumours would appear to be related most closely to the 'standard type sporadic CRC' (group 4). In fact, as CIN was observed frequently in groups 2 and 3, it could be argued that CIMP would be relevant for CRC carcinogenesis only if the MLH1 gene promoter is affected, although global expression analyses have shown unique gene expression patterns for CIMP-high tumours without MSI-H (20).…”
Section: Discussionmentioning
confidence: 99%